Amelioration of premature aging in Werner syndrome stem cells by targeting SHIP/AKT pathway - Hei-Yin Tam; Jiaxing Liu; Tsz-Ching Yiu; Adrian On-Wah Leung; Chang Li; Shen Gu; Owen Rennert; Boxian Huang; Hoi-Hung Cheung (Cell & Bioscience)
Abstract Background Pathogenic or null mutations in WRN helicase is a cause of premature aging disease Werner syndrome (WS). WRN is known to protect somatic cells including adult stem cells from premature senescence. Loss of WRN in mesenchymal stem cells (MSCs) not only drives the cells to premature senescence but also significantly impairs the function of the stem cells in tissue repair or regeneration. Results In this study, we profiled the signaling pathways altered in WRN-deficient MSC and applied pharmacological method to activate the AKT signaling in these cells and examined their cellular phenotype related to aging. We found that the AKT signaling in WRN-deficient MSCs was significantly suppressed while the AKT upstream phosphatases (SHIP1/2) were upregulated. Knockdown or inhibition of SHIP1/2 could ameliorate premature senescence in WRN-deficient MSCs. Moreover, SHIP inhibition stimulated MSC proliferation and suppressed expression of pro-inflammatory cytokines IL-6 and IL-8. The stemness of WRN-deficient MSC was also improved upon pharmacological treatments with the inhibitors. Conclusions These results suggested that targeting the SHIP/AKT signaling pathway is beneficial to WRN-deficient stem cells and fibroblasts, which might be applied for improving the trophic function of MSC in, for instance, promoting angiogenesis.